Alexei Navalny, Russia's most vociferous Putin critic - BBC News (BBC News, 2011)
Russian anti-corruption campaigner Alexei Navalny was the main opposition threat to the Kremlin.
Russian Federation

The Archive in the Witness: Documentation in Settings of Chronic Insecurity - Riaño-Alcalá, Pilar; Baines, Erin (International Journal of Transitional Justice, 2011)
Abstract1. Through an exchange between members of community-based organizations that document human rights violations in northwest Colombia and northern Uganda
Other Publications

Toward an understanding of archives as a feature of collective memory - Josias, Anthea (Archival Science, 2011)
This paper reviews important aspects of the literature on collective memory, how some of these concerns have been expressed in archives, and contemplates how these issues relate to the politically transformative South African post-apartheid context. It highlights the erosion of boundaries between archives, museums, and other less-institutionalized memory projects in post-apartheid South Africa. It notes ways in which archival activity is taking place outside of traditional archives, as part of a changing and evolving memory landscape. It acknowledges the significant gaps in the written record that are a result of apartheid practices and cites different approaches that were overlooked by apartheid’s official archival systems. This paper offers a way of contemplating the ‘social constructedness’ of collective memory and the social and political dimensions of archives.
Other Publications
Keywords: Collective memory; Personal testimonies; Political transformation; Politics of memory; Social memory; South Africa

Secrets and Files: Access to Archives in Italy from WWII to the Present - Barrera, Giulia (Acervo. Revista do Arquivo Nacional, 2011)
Other Publications

Admissibility of electronic documentation as evidence in U.S. courts - Thomson, Lucy L (Human Rights Electronic Evidence Study, Center for Research Libraries, 2011)
Other Publications

Securing the Communist State: The Reconstruction of Coercive Institutions in the Soviet Zone of Germany and Romania, 1944–1948 - Van De Grift, Liesbeth (Lexington Books, 2011)
From Berlin to Bucharest, from Warsaw to Sofia, Soviet tanks crossed national borders across East Central Europe at the end of the Second World War. The arrival of the Red Army marked an important turn in history. Within only a few years, the often unpopular communist parties developed into political organizations with mass followings. They managed to seize power, eliminate political opposition to their rule, and purge the state apparatus of undesirable personnel. In Securing the Communist State, Liesbeth van de Grift provides a new understanding of these organizations using recently disclosed material from the communist archives in Berlin and Bucharest. She reveals how these communist parties gained control over the security apparatus after 1945 in East Central Europe from a transitional justice perspective, focusing on purges and personnel policies. This book shows that the personal break after 1945 was not as radical as is often thought.
Keywords: References - Boel et al. (2021); Archives and Human Rights

History textbooks and the wars in Asia: divided memories - Shin, Gi-Wook; Sneider, Daniel C. (Routledge, 2011)
OCLC: ocn651914367
Keywords: 20th century; East Asia; Historiography; History; Military Historiography; History; Military Study and teaching (Secondary); History; Military Textbooks; Nationalism and education; Nationalism and historiography; References - Boel et al. (2021); Archives and Human Rights; Social aspects

NARRATIVES AND BILATERAL RELATIONS: RETHINKING THE “HISTORY ISSUE” IN SINO- JAPANESE RELATIONS - Gustafsson, Karl (Stockholm University, 2011)
Keywords: References - Boel et al. (2021); Archives and Human Rights

Appendix A to Part 74 - Declarations of Eligibility by Persons Identified by the Office of Redress Administration and Requests for Documentation - Code of Federal Regulations (govinfo.gov, 2011)
Keywords: References - Boel et al. (2021); Archives and Human Rights

History - The Conference on Jewish Material Claims against Germany (Claims Conference, 2011)
A history of the Claims Conference since its founding in 1951 and the formation of the Conference on Jewish Material Claims Against Germany.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Report of the Special Representative of the SecretaryGeneral on the issue of human rights and transnational corporations and other business enterprises - Guiding Principles on Business and Human Rights: Implementing the United Nations “Protect, Respect and Remedy” Framework - Ruggie, John (United Nations, 2011)
Keywords: References - Boel et al. (2021); Archives and Human Rights

Political Effects: Trust in Government - Roman, David (Lustration and Transitional Justice: Personnel Systems in the Czech Republic, Hungary, and Poland., 2011)
Keywords: References - Boel et al. (2021); Archives and Human Rights

solution adopted by the Human Rights Council - 18/7 Special Rapporteur on the promotion of truth, justice, reparation and guarantees of non-recurrence - Human Rights Council (United Nations, 2011)
Keywords: References - Boel et al. (2021); Archives and Human Rights

Network of information and counter information on the military regime in Brazil (1964-1985) - Unesco (UNESCO, 2011)
UNESCO is the United Nations Educational, Scientific and Cultural Organization. It seeks to build peace through international cooperation in education, the sciences, culture and communication. UNESCO’s programmes contribute to the achievement of the Sustainable Development Goals defined in Agenda 2030, adopted by the UN General Assembly in 2015. Serving as a laboratory of ideas, UNESCO helps countries adopt international standards and manages programmes that foster the free flow of ideas and knowledge sharing. In this spirit, it develops educational tools to help people live as global citizens free of hate and intolerance. UNESCO works so that each child and citizen has access to quality education. By promoting cultural heritage and the equal dignity of all cultures, it strengthens bonds among nations. UNESCO fosters scientific programmes and policies that support development and cooperation. UNESCO stands up for freedom of expression, as a fundamental right and a key condition for democracy and development.
Keywords: References - Boel et al. (2021); Archives and Human Rights

ICA Human Rights Archives Directory - HRWG ICA (Human Rights Working Group - International Council on Archives) (Archivists Watch, 2011)
For some years now, the ICA Human Rights Working Group (HRWG) has been trying to establish a directory of human rights archives from around the globe. This summer, I began volunteering with the IC…
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Guiding Principles on Business and Human Rights: Implementing the United Nations ‘Protect, Respect and Remedy’ Framework - United Nations Human Rights (United Nations, 2011)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Saudi king gives women right to vote - Alsharif, Asma (Reuters, 2011)
Saudi Arabia's king announced on Sunday women would be given the right to vote and stand in elections, a bold shift in the ultra-conservative absolute monarchy as pressure for social and democratic reform sweeps the Middle East.
Keywords: KING; References - Comma (2020 1-2); Archives and Human Rights; SAUDI; US; WOMEN

Property Lost in Holocaust Is Cataloged Online - Kershner, Isabel (The New York Times, 2011)
The database, listing more than half a million pieces of property, is part of a new project, financed by the Israeli government, to harness technology in the struggle for restitution.
Keywords: Computers and the Internet; Holocaust and the Nazi Era; Israel; Jewish Agency for Israel; References - Comma (2020 1-2); Archives and Human Rights; Reparations and Restitution

De Jure Statelessness in the Real World: Applying the Prato Summary Conclusions - Bingham, Laura; Harrington Reddy, Julia; Köhn, Sebastian (Open Society Foundations, 2011)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

The Evolution of International Human Rights: Visions Seen - Lauren, Paul Gordon (University of Pennsylvania Press, 2011)
This widely acclaimed and highly regarded book, used extensively by students, scholars, policymakers, and activists, now appears in a new third edition. Focusing on the theme of visions seen by those who dreamed of what might be, Lauren explores the dramatic transformation of a world patterned by centuries of human rights abuses into a global community that now boldly proclaims that the way governments treat their own people is a matter of international concern-and sets the goal of human rights "for all peoples and all nations." He reveals the truly universal nature of this movement, places contemporary events within their broader historical contexts, and explains the relationship between individual cases and larger issues of human rights with insight. This new edition incorporates material from recently declassified documents and the most recent scholarship relating to the creation of the new Human Rights Council and its Universal Periodic Review, the International Criminal Court, the Responsibility to Protect (R2P), terrorism and torture, the impact of globalization and modern technology, and activists in NGOs devoted to human rights. It provides perceptive assessments of the process of change, the power of visions and visionaries, politics and political will, and the evolving meanings of sovereignty, security, and human rights themselves.
Keywords: References - Comma (2020 1-2); Archives and Human Rights

News from the ICA Human Rights Working Group - 2011-12 (December) - Peterson, Trudy Huskamp (ICA, 2011)

News from the ICA Human Rights Working Group - 2011-11 (November) - Peterson, Trudy Huskamp (ICA, 2011)

News from the ICA Human Rights Working Group - 2011-10 (October) - Peterson, Trudy Huskamp (ICA, 2011)

News from the ICA Human Rights Working Group - 2011-09 (September) - Peterson, Trudy Huskamp (ICA, 2011)

News from the ICA Human Rights Working Group - 2011-08 (August) - Peterson, Trudy Huskamp (ICA, 2011)

News from the ICA Human Rights Working Group - 2011-07 (July) - Peterson, Trudy Huskamp (ICA, 2011)

News from the ICA Human Rights Working Group - 2011-06 (June) - Peterson, Trudy Huskamp (ICA, 2011)

News from the ICA Human Rights Working Group - 2011-05 (May) - Peterson, Trudy Huskamp (ICA, 2011)

News from the ICA Human Rights Working Group - 2011-04 (April) - Peterson, Trudy Huskamp (ICA, 2011)

News from the ICA Human Rights Working Group - 2011-03 (March) - Peterson, Trudy Huskamp (ICA, 2011)

News from the ICA Human Rights Working Group - 2011-02 (February) - Peterson, Trudy Huskamp (ICA, 2011)

News from the ICA Human Rights Working Group - 2011-01 (January) - Peterson, Trudy Huskamp (ICA, 2011)